TU2.13 Laparoscopic/robotic restorative proctectomy in the District General Hospital setting. (9th August 2022) - Patel, Maitreyi; Aguayo, Xavier; Robinson, Christine; Banerjee, Saswata; Hanson, Matthew; Rajendran, Nirooshun
Abstract: Aims: Ileal pouch anal anastomosis/restorative proctectomy is a standard surgical treatment for ulcerative colitis performed in a few specialist centres. We report the evolution of the service at our trust which originally carried out open pouch surgery but has moved practice towards laparoscopic and robotic-assisted pouch surgery. The aim of this study was to assess the surgical and functional outcomes of patients undergoing laparoscopic/robotic-assisted IPAA. Methods: Data were prospectively collected from consecutive laparoscopic/robotic IPAA cases from 2014 to 2021. Patient demographics, operative details, postoperative complications, functional outcomes were collected. Patients were selected by IBD specialized surgeons and reviewed by a pouch nurse. Follow-up consisted of clinical examination and assessment of pouch function. Results: 18 patients underwent laparoscopic or robotic IPAA during the study period, 13 (72.23%) were males. Median age was 28 years. Indication for surgery was ulcerative colitis. Median duration of surgery was 7 hours. Four patients (22.23%) developed postoperative intra-abdominal collection, managed conservatively in all except one, who required laparoscopic washout. The median duration of stay was 8 days. The rate of severe complications, Grade 3 and 4 on Clavien-Dindo classification was 11.12%. During a median follow up of 75 months, there were no pouch failures. The median stool frequency was 6 daily. Conclusion: Our data suggests that with good patient selection and guidance from an experienced pouch nurse, laparoscopic/robotic IPAA is safe and feasible. Good perioperative outcomes and acceptable pouch function can be achieved in a DGH setting with a team to ensure consistent care of patients.